Monitoring photobleaching and hemodynamic responses to HPPH-mediated photodynamic therapy of head and neck cancer: a case report - Sunar, Ulas (2010)
We present initial results obtained during the course of a Phase I clinical trial of 2-1[hexyloxyethyl]-2-devinylpyropheophorbide-a (HPPH)-mediated photo-dynamic therapy (PDT) in a head and neck cancer patient. We quantified blood flow, oxygenation and HPPH drug photobleaching before and after therapeutic light treatment by utilizing fast, non-invasive diffuse optical methods. Our results showed that HPPH-PDT induced significant drug photobleaching, and reduction in blood flow and oxygenation suggesting significant vascular and cellular reaction. These changes were accompanied by cross-linking of the signal transducer and activator of transcription 3 (STAT3), a molecular measure for the oxidative photoreaction. These preliminary results suggest diffuse optical spectroscopies permit non-invasive monitoring of PDT in clinical settings of head and neck cancer patients.